3, 4, 5‐Tricaffeoylquinic Acid Attenuates TRAIL‐induced Apoptosis in Human Keratinocytes by Suppressing Apoptosis‐related Protein Activation. (30th July 2015) - Lee, Da Hee; Nam, Yoon Jeong; Lee, Min Sung; Sohn, Dong Suep; Shin, Yong Kyoo; Lee, Chung Soo
<x xml:space="preserve">Abstract</x> Caffeoyl derivatives exhibit antiinflammatory and antioxidant effects. However, the effect of 3, 4, 5‐tricaffeoylquinic acid on the tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL)‐induced apoptosis in keratinocytes that may be involved in skin diseases has not been studied. In this respect, we investigated the effect of 3, 4, 5‐tricaffeoylquinic acid on TRAIL‐induced apoptosis in human keratinocytes. 3, 4, 5‐Tricaffeoylquinic acid and oxidant scavengers attenuated the decrease in the cytosolic levels of Bid, Bcl‐2, and survivin proteins; the increase in the levels of cytosolic Bax, p53, and phosphorylated p53; the increase in the levels of phosphorylated p38; the increase in the mitochondrial levels of the voltage‐dependent anion channel; loss of the mitochondrial transmembrane potential; the release of cytochrome c; activation of caspases (8, 9, and 3); cleavage of poly [ADP‐ribose] polymerase‐1; production of reactive oxygen species; the depletion of glutathione (GSH); nuclear damage; and cell death in keratinocytes treated with TRAIL. These results suggest that 3, 4, 5‐tricaffeoylquinic acid may reduce TRAIL‐induced apoptosis in human keratinocytes by suppressing the activation of the caspase‐8 and Bid pathways and the mitochondria‐mediated cell death pathway. The effect appears to be associated with the inhibitory effect on the production of reactive oxygen species and depletion of GSH. 3, 4, 5‐Tricaffeoylquinic acid appears to be effective in the prevention of TRAIL‐induced apoptosis‐mediated skin diseases. Copyright © 2015 John Wiley & Sons, Ltd.